SOME RECENT CHANGES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE IN THE HIGH SCHOOLS OF ELBASAN - Josilda Papajani (European Scientific Journal, ESJ, 2014)
In the past decade all the Albanian Education has undergone a period of significant change, in terms of new developments. These developments are almost entirely due to the fact that methods and methodologies changed rapidly their way of being used by the teachers and textbooks, as well. The process of changes in the Albanian Education System has touched even the English Language Curriculum. Despite other factors which seem to be main ones in reshaping the curriculum, a great emphasis is given even to the modernization of classroom environment and to the modernization of methods within themselves, as well. Teachers and institutions can influence the student’s willingness to learn through the way they organize the lesson: from teacher-centered to student-centered; from passive teaching to an active one; from an authoritarian environment to a positive one. Methods play a major role in the way our students acquire the foreign language, too. That is why certain methods tend to change within themselves, such as the example of the creation of Pimsleur method.